The effect of COVID-19 on dental treatment under conscious sedation in children: a retrospective study at Dental University Hospital, Riyadh, Saudi Arabia - Aldowsari, Mannaa K.; Sulimany, Ayman M.; Bin Saleh, Saad S.; Alhussain, Modhi; Alsuhaibani, Daniyah; Alwasil, Wasayef; Hamdan, Hebah M. (International Journal Of Community Medicine And Public Health, 2023)
Background: This study aimed to assess the effect of the COVID-19 pandemic on the number of cases and types of dental procedures performed under conscious sedation for children at Dental University Hospital (DUH), Riyadh, Saudi Arabia during the period between 2019-2021. Methods: This retrospective chart review study used digital and paper records for data collection. The sample was comprised of children aged 3 to 11 years of age who received dental treatment under conscious sedation from 2019 to 2021 at DUH. Descriptive statistics were presented, and negative binomial regression analysis was performed to assess the difference in the number of performed procedures by different academic year. Results: Two hundred and twenty-seven subjects had dental treatment under conscious sedation from 2019 to 2021. Most of the sample were Saudi (88.5%) and classified as ASA I (97.8%). The number of sedation cases were almost 55% lower than the number of cases that were done in 2020 and almost 62% lower than the cases that were performed in 2019. There was a significant decrease in the pulp therapy and preventive procedures (p=0.03, and p=0.02, respectively). No statistically significant differences were found in other procedures. Conclusions: There was a considerably huge decrease in the number of cases treated under conscious sedation as an effect of the pandemic. Pulp therapy and preventive procedures were the most affected. Our findings indicate the need to establish a protocol for delivering dental care while ensuring the safety of the patients in such difficult situations.